An artificial nail disorder - (:unkn) unknown (My University, 2010)
Cutaneous artefactual diseases are self-inflicted dermatoses affecting pediatric patients as well as adults. They can vary from strange morphology, and bizarre shapes to disfiguring skin ulcerations. The nails may also be involved. A child with nail growth arrest, an unusual feature, which has not been reported before is described. Pediatric artefactual diseases are simply a cry for help. A multidisciplinary approach involving the pediatrics, dermatology and psychiatry units may help resolving the problem.
Keywords: Artificial nail disorder; Factitious; Nail biting; Nail picking; Self-inflected dermatose